Wilber's war : an American family's journey through World War II - Bradt, Hale, 1930- (Salem, MA : Van Dorn Books, 2016)
Wilber's War chronicles the story of two ordinary Americans, Wilber and Norma Bradt, during an extraordinary time, World War II. It offers fresh insight--deeply personal --into the historic conflict as it was fought by the U.S. Army in the Pacific Theater and by a family on the home front. It is an epic tale of duty, heroism, love, infidelity, and the tragedy of suicide.
Book 1: Citizen soldier -- Book 2: Combat and new life -- Book 3: Victory and homecoming.
Keywords: Bradt, Wilber, -- 1900-; World War, 1939-1945 -- Personal narratives, American; World War, 1939-1945 -- Campaigns -- Pacific Area; World War, 1939-1945 -- Campaigns -- Philippines; Soldiers -- United States -- Biography